Structural and Biocidal Studies of Organotin(IV) Complexes of Triazene-1-Oxides - Sharma, R.; Thakur, A.K.; N. Choudhary, S. (Asian Journal of Chemistry, 2010)
Five co-ordinate and six co-ordinate complexes of triorganotin(IV) and diorganotin(IV) involving variedly substituted monobasic bidentate triazene-1-oxides (TH) have been synthesised. Trigonal bipyramidal structure for five co-ordinate and trans-diorgano octahedral structure for six co-ordinate complexes have been assigned on the basis of analytical data, conductance values, molecular complexities in freezing benzene IR and Mössbauer spectral data. Antibacterial activity of triazene-1-oxides, organotin(IV) compounds R3SnX2 and R3SnX and organotin(IV) complexes of triazene-1-oxides R2SnT2, and R3SnT were examined using Agar-plate diffusion technique. Following order of biocidal activity has been found: R2SnX2 < TH < R3SnX < R2SnT2 < R3SnT